Isolated Testicular Metastasis Diagnosed More than a Decade and a Half Post Primary Treatment for Prostate Cancer - Nassib F. Abou Heidar; Gerges Bustros; Jose M. El-Asmar; Bassel Zein Sabatto; Jad A. Degheili (Case Reports in Oncological Medicine)
Prostate cancer is the most common visceral malignancy among men. It rarely metastasizes to the testicles. We herein present the case of a male patient who underwent a radical prostatectomy for a grade group 3 Gleason score 7 (4+3) prostate adenocarcinoma followed by adjuvant radiation therapy and continuous androgen deprivation therapy after his first biochemical recurrence. Despite optimal management, prostate-specific antigen (PSA) levels rose back up, upon which a PET/CT 68Gallium scan demonstrated an isolated left testicular lesion that turned out to be of prostatic origin following orchiectomy. Testicular metastases from prostate cancer are of unknown prognosis, and the current treatment modality favors an orchiectomy.